E. W. Nelson's notes on the Indians of the Yukon and Innoko Rivers, Alaska / Fieldiana, Anthropology, v. 70 - Nelson, Edward William, 1855-1934.; VanStone, James W. editor (Chicago : Field Museum of Natural History, 1978)
Includes bibliographical references (p. 74-77) and index. Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).